(untitled) (Research, Society and Development, 2020)
This research investigated the teaching of chemistry teaching, in the context of using experimental activities as a teaching and learning tool in high school chemistry classes. It aims to contribute to the positive performance of students in the 3rd year of high school, through practical classes. The research methodology is characterized as basic, quantitative, exploratory, and hypothetical-deductive, running through the descriptive character, involving an action research. The study was developed with 30 students from the 3rd year of high school at a high school located in the municipality of Iguatu / CE. The main results were: 47% of students have greater difficulty in interpreting chemistry questions, 48% of students prefer the methodology used by the teacher in the classroom as the participatory one, 83% of students affirm that practical laboratory classes help the relationship a lot theory and practice for establishing knowledge in the discipline of chemistry, 100% of the students affirmed the positive contribution of the classes taught by the trainees to learning. In this context, this research suggests that there are challenges that must be faced by the teacher and that the teacher should always look for ways to motivate and attract students’ attention to the contents seen in the classroom. Thus, it can be concluded that there is a positive effect of performing experimental activities as a teaching and learning tool in high school chemistry classes.